Rett-ов синдром - Трајковски, Владимир (Филозофски факултет, Скопје, 2006)
Rett syndrome is a sporadic disorder (except for a few familial cases) occuring in 1 in 10.000 to 1 in 23.000 girls worldwide. In 1999, mutations in the methyl-CpG binding protein 2 gene (MECP2) were identified as the primary cause of Rett syndrome. The syndrome ’s pathophysiology suggests that early hypofunction of 'aminergic nurons interferes with the development of higher neuronal systems. Most girls with Rett syndrome develop normally prior to the appearance of the typical symptoms. It is unique neurodevelopmental disorder, with onset of hypotonia, autistic tendency, and abnormalities of fine finger movements and gross movements of the arms in early infancy. Clinical features include specific age-dependent symptoms. This syndrome is associated with profound mental and motor handicap. The neuropathology of Rett syndrome involves individual neurons, perhaps selected neurons, of decreased size, and dendritic branching. Clinical diagnosis requires strict application of the consensus criteria for classic and variant Rett syndrome. Rett syndrome is not curable today. It needs a continual and complex treatment, aimed to save or prolong ambulation and communication, and to minimize epileptic, nutritional, orthopaedic and other complications.
Rett syndrome
Keywords: Rett-ов синдром, мутација, MECP2 ген, невроразвојно нарушување